Improved 11-year solar signal in the Freie Universität Berlin Climate Middle Atmosphere Model (FUB-CMAM) - Matthes, K; Langematz, U; Gray, L; Kodera, K; Labitzke, K (2004)
So far, general circulation model studies have not been able to capture the magnitude and characteristics of the observed 11-year solar signal in the stratosphere satisfactorily. Here results from model experiments with the Freie Universität Berlin Climate Middle Atmosphere Model are presented that are in considerable agreement with observations. The experiments used realistic spectral solar irradiance changes, ozone changes from a two-dimensional radiative-chemical-transport model, and a relaxation toward observed equatorial wind profiles throughout the stratosphere. During Northern Hemisphere winter a realistic poleward downward propagation of the polar night jet (PNJ) anomalies, significantly weaker planetary wave activity, and a weaker mean meridional circulation under solar maximum conditions are reproduced in the model. The observed interaction between the Sun and the Quasi-Biennial Oscillation (QBO) is captured and stratospheric warmings occur preferentially in the west phase of the QBO. Only the magnitude of the anomalies during the dynamically active season improves, whereas the summer signal and the signal at low latitudes are still too weak. The results emphasize the important role of equatorial winds in achieving a more realistic solar signal by producing a more realistic wind climatology. Furthermore, they confirm recent results that equatorial winds in the upper stratosphere, the region dominated by the Semiannual Oscillation, are an important factor in determining interannual variability of the PNJ. Copyright 2004 by the American Geophysical Union.